The importance of socio-cultural factors as determinants of the attractiveness of the fintech sector offer for individual clients of banks - Świeszczak, Krzysztof (Journal of Finance and Financial Law, 2025)
The purpose of the article. The aim of this publication is to analyze the importance of socio-cultural factors for assessing the attractiveness of the FinTech sector's offer among individual clients of the banking sector and the FinTech sector. The following hypothesis was put forward in the article: the average level of importance of socio-cultural factors for assessing the attractiveness of the FinTech sector's offer does not statistically differ significantly for individual customers of the banking sector and individual customers of both, the banking sector and the FinTech sector. Methodology. In order to verify the adopted hypothesis and achieve the purpose of this publication, 240 direct individual questionnaire interviews (PAPI interviews – Paper & Pen Personal Interviews) were conducted among customers of the banking sector, and it should be noted that the study, due to the representativeness of the conducted research, involved: • 120 individual clients of the banking sector who have not yet used the offer of the FinTech sector; • 120 individual clients of the banking sector with experience in using the offer of the FinTech sector. The questionnaire survey was preceded by in-depth interviews with experts, representatives of the scientific community professionally involved in research on the functioning of FinTech enterprises as well as owners and co-owners of business entities belonging to the FinTech sector. Results of the research. Based on the conducted research, it was found that individual clients of the banking sector who had not yet used the FinTech sector's offer were more likely to agree with two statements, i.e., the stronger the bank client's sense of belonging to a selected social group, the higher the assessment of the attractiveness of the FinTech sector's offer and the stronger the bank customer's identification with family values, the higher the assessment of the attractiveness of the FinTech sector's offer. In the case of responses to the remaining statements, no statistically significant differences were noted. The result of the analyzes carried out in this article is a positive verification of the research hypothesis according to which the average level of importance of socio-cultural factors for assessing the attractiveness of the FinTech sector offer does not differ in a statistically significant way for individual customers of the banking sector and individual customers of the banking sector and FinTech sector.